Die neo-Kantiaanse historiese kennisleer van die Badenskool: Heinrich Rickert (Historia, 2021)
This article deals with the epistemology of Heinrich Rickert. Rickert's aim, to establish history as a science free from positivism, led to an elaboration of the ideas of Windelband and Lask. Hence Rickert formulated a theory of concept formation emphasising the unique characteristics of historical phenomena. For Rickert the main problem of historical knowledge is the distinction between significant and insignificant phenomena. In his attempt to solve this problem, Rickert invented "value relevance" as criterion for selecting significant objects from empirical reality. However, Rickert's claim that the objectivity of history is dependent on the distinction between value relevance and value-judgements is not convincing.
Keywords: Value judgments; Historical epistemology; Rickert, H.; History; Baden School